1035325 Faktor-faktor yang Berhubungan dengan Pemeriksaan Antenatal Care (ANC) Pada Ibu Hamil di Klinik Bersalin Titi Safitri Kota Jambi Tahun 2019 - Rubiyati (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2019)
Abstract According to data from basic health research (Ristekdas) in 2013, almost all pregnant women in Indonesia (95.4%) had already performed antenatal care (K1) with a frequency of at least 4 times during her pregnancy period of 83.5%. As for the scope of the first examination at the first examination is 81.6% and the frequency of ANC 1-1-2 or K4 (at least 1 time in the first trimester, at least 1 time in the second trimester and at least 2 times in the third trimester) of 70.4%. This research is an analytical research with cross sectional approach, which is a study to study the dynamics of the correlation between risk factors and effects, by way of approach, observation or data collection at the same time / point time approach. The sample in this study amounted to 30 respondents, the variables used were knowledge, attitudes, socioeconomic, husband support, and experience. The results of the study are that there is a significant relationship between knowledge, attitude, socioeconomic, husband's support, experience with ANC examination in pregnant women at the Titi Safitri Maternity Clinic in Jambi City in 2019. It is hoped that this research can add to the knowledge of pregnant women about the importance of antenatal care for early detection of abnormalities and problems that can occur during pregnancy Keywords : Knowledge, Attitude, Socio-Economy, Husband Support, Experience, ANC Examination